Accumulation of long-lived mRNAs associated with germination in embryos during seed development of rice. (4th May 2015) - Sano, Naoto; Ono, Hanako; Murata, Kazumasa; Yamada, Tetsuya; Hirasawa, Tadashi; Kanekatsu, Motoki
Highlight: Long-lived mRNAs stored in dry seed are translated after imbibition for germination. We report accumulation of long-lived mRNAs in developing rice embryos and candidates of the mRNAs required for germination. Abstract: Mature dry seeds contain translatable mRNAs called long-lived mRNAs. Early studies have shown that protein synthesis during the initial phase of seed germination occurs from long-lived mRNAs, without de novo transcription. However, the gene expression systems that generate long-lived mRNAs in seeds are not well understood. To examine the accumulation of long-lived mRNAs in developing rice embryos, germination tests using the transcriptional inhibitor actinomycin D (Act D) were performed with the Japonica rice cultivar Nipponbare. Although over 70% of embryos at 10 days after flowering (DAF) germinated in the absence of the inhibitor, germination was remarkably impaired in embryos treated with Act D. In contrast, more than 70% of embryos at 20, 25, 30 and 40 DAF germinated in the presence of Act D. The same results were obtained when another cultivar, Koshihikari, was used, indicating that the long-lived mRNAs required for germination predominantly accumulate in embryos between 10 and 20 DAF during seed development. RNA-Seq identified 529 long-lived mRNA candidates, encoding proteins such as ABA, calcium ion and phospholipid signalling-related proteins, and HSP DNA J, increased from 10 to 20 DAF and were highly abundant in 40 DAF embryos of Nipponbare and Koshihikari. We also revealed that these long-lived mRNA candidates are clearly up-regulated in 10 DAF germinating embryos after imbibition, suggesting that the accumulation of these mRNAs in embryos is indispensable for the induction of germination. The findings presented here may facilitate in overcoming irregular seed germination or producing more vigorous seedlings.